Two new species of Begonia (sect. Platycentrum, Begoniaceae) from the Central Highlands of Vietnam: B. villosula and B. lophura - Hoang, Thanh Son; Lin, Che-Wei (Phytotaxa, 2021)
Two new species of Begonia L., namely Begonia villosula T.S.Hoang & C.W.Lin and B. lophura T.S.Hoang & C.W.Lin, from the Central Highlands of Vietnam, are described and illustrated. They are assigned to Begonia sect. Platycentrum based on several characters including axillary inflorescence, 4-tepaled staminate flower and 5-tepaled pistillate flower with bilocular ovary, each with two placentae. Begonia villosula resembles B. thomsonii, but it is different in its leaf margins crenate to crenulate (vs. irregularly serrulate), stamens 80–120 (vs. 35–70), pistillate flower 4-tepaled (vs. 5-tepaled) and ovary hirsute (vs. villous). Begonia lophura is somewhat similar to B. pavonina, but it is different in having widely ovate (vs. ovate) and abaxially red hirsute (vs. glabrous) leaves, bracts persistent (vs. caducous), tepals hirsute (vs. glabrous) in both of staminate and pistillate flowers, capsule scabrous (vs. glabrous) and abaxial wing strongly swollen (vs. thin, not swollen). The conservation status of the two new species are assessed as Vulnerable according to the IUCN Red List criteria.